High-pressure synthesis of boron-rich chalcogenides B12S and B12Se - Cherednichenko, Kirill A.; Mukhanov, Vladimir A.; Kalinko, Aleksandr; Solozhenko, Vladimir L. (Elsevier, 2022)
Two boron-rich chalcogenides B12S and B12Se isostructural to α-rhombohedral boron were synthesized by chemical reaction of the elements at high-pressure – high-temperature conditions. The crystal structures and stoichiometries of both compounds were confirmed by Rietveld refinement of synchrotron X-ray diffraction data and elemental analysis. The experimental Raman spectra of B12S and B12Se were investigated for the first time. All observed Raman bands have been attributed to the theoretically calculated phonon modes, and the mode assignment has been performed.--//-- This is accepted version of the article Kirill A. Cherednichenko, Vladimir A. Mukhanov, Aleksandr Kalinko, Vladimir L. Solozhenko; High-pressure synthesis of boron-rich chalcogenides B12S and B12Se; Journal of Alloys and Compounds, Volume 898, 2022, 162874, ISSN 0925-8388, https://doi.org/10.1016/j.jallcom.2021.162874.(https://www.sciencedirect.com/science/article/pii/S0925838821042845). Published under the CC BY-NC-ND license.
The authors thank Drs. I. Dovgaliuk and T. Chauveau for assistance with Rietveld analysis; and Drs. V. Bushlya and A. Jamali for help with EDX/SEM measurements. This work was financially supported by the European Union's Horizon 2020 Research and Innovation Program under Flintstone2020 project (grant agreement No 689279).
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Boron-rich chalcogenides; High-pressure synthesis; Crystal structure; Raman spectra